Effect of Macro-Micro Nutrients and Liming on Winter Season Kusmi Lac Yield on Flemingia semialata - Ghosal, S.; Meena, S. C.; Lohot, V. D.; Thamilarashi, K. (Indian Forester, 2017)
Effect of liming and application of different macro/ micro nutrients on lac yield of Flemingia semialata plants were evaluated by an experiment consisted 12 treatments/ combinations. These included recommended doses of Zinc, Copper, Boron, Molybdenum; liming @ 125 g/m2, two doses of potassium (30 and 60 g/plant), two doses of nitrogen (25 and 50 g/plant), combination of N-P-K (50, 25 and 50 g/ plant) and two control treatments (lac inoculated and lac uninoculated) replicated thrice in Randomized Block Design. Treatments like liming, two doses of potassium (30 and 60 g/ plant) and nitrogen application @ 25 g/ plant produced very low yield ration but high sticklac productivity. While all micro nutrient applied treatments and control produced relatively higher yield ratio but significantly lower stick lac production. Higher rate of nitrogen application and NPK combination are the inferior most treatments as they produced both yield ratio and sticklac yield in lower side. Higher sticklac yield on treatments like lime, potassium application, etc. signified that encrustation was quite dense and thick with those treatments. This finding inferred that these treatments are congenial for satisfactory lac production. Liming and potassium application @ 30 g/ plant registered a significant increase of 41 and 48 per cent increases in sticklac production over control. Spraying boron and molybdenum proved to be much better than spray of zinc and copper. However, output from control plants were in between and remained at par to both the groups.